Spatial distribution of child malnutrition in Yerba Buena, Tucumán, Argentina (2014-2015). - Cordero, María Laura (2017)
The maps constitute an instrument for the knowledge and the management of the territory, nevertheless its incursion in the study of the nutrition is recent. Objective: The objective of this work was to explore and describe the spatial distribution of child malnutrition in urban and rural areas of the department of Yerba Buena, Tucumán, Argentina. Methods: An exploratory, cross-sectional ecological study was perform, where the minimum geostatistical unit of census aggregation (census radio) was analyzed. Results: Indicators of malnutrition, undernutrition and excess weight were developed and spatialized in the school aged population evaluated during the period 2014-15. The bottom-up analysis on small scales allowed determining the percentage, intensity and typology in each geographical unit, illustrating the territorial disparities of the anthropometric parameters. This work constitutes an approach to the study of child malnutrition from a geographic perspective. Conclusions: The high descriptive value of the cartography will allow advancing in the knowledge of the spatial distribution of the nutritional status in different population. GIS are useful tools that facilitate the understanding of the epidemiological profile of events in the health of individuals, which can be used in the design, monitoring and evaluation of public policies